Penentuan Customer Terbaik Menggunakan Metode SAW Pada CV ABC di Palembang - Yulianus Jonathan Davlin; Fransiska Prihatini Sihotang (MDP Student Conference, 2026)
This study aims to develop a web-based Decision Support System (DSS) to address the previously subjective evaluation of CV ABCs business partners. The scope of the study includes an assessment based on five criteria, consisting of benefits and costs. These five criteria include affiliation, turnover, payment precision, total returns, and subscription length. The system development method uses the Rational Unified Process (RUP) with the Laravel and MySQL frameworks, while decision calculations use the Simple Additive Weighting (SAW) method. Each of the five criteria has sub-criteria with varying ranges according to the company's policies and actual circumstances. Based on Black Box testing, the system functions well. It is concluded that this system helps management determine appropriate marketing strategies, such as providing discounts, to increase loyalty and business competitiveness.